Household debt sustainability: what explains household non-performing loans? An empirical analysis - Laura Rinaldi; Alicia Sanchis-Arellano (European Central Bank (ECB), 2006)
Sound household financial conditions are relevant for both financial and monetary stability. Therefore, we analyse household financial fragility in a sample of euro area countries with the aim to shed some light on the nature of the large debt increase accumulated in recent years. We focus on household arrears on payment obligations, which are one of the most direct measures of financial stress of the sector. The probability of falling into arrears is derived from a life-cycle type of model and is investigated empirically using a cross-section and time series approach. We analyse cointegration and model arrears within an errorcorrection framework. The results suggest that the financial conditions of households might become more vulnerable to adverse shocks in their income and wealth.
Keywords: C23; G21; D14; 330; default; household debt sustainability; non-performing loans; Panel Cointegration; Private Verschuldung; Privater Haushalt; Schock; Einkommenseffekt; Vermögenseffekt; Theorie; EU-Staaten